DNA polymerase gamma mutations that impair holoenzyme stability cause catalytic subunit depletion. Issue 9 (6th May 2021) - Silva-Pinheiro, Pedro; Pardo-Hernández, Carlos; Reyes, Aurelio; Tilokani, Lisa; Mishra, Anup; Cerutti, Raffaele; Li, Shuaifeng; Rozsivalova, Dieu-Hien; Valenzuela, Sebastian; Dogan, Sukru A; Peter, Bradley; Fernández-Silva, Patricio; et al.
Abstract: Mutations in POLG, encoding POLγA, the catalytic subunit of the mitochondrial DNA polymerase, cause a spectrum of disorders characterized by mtDNA instability. However, the molecular pathogenesis of POLG -related diseases is poorly understood and efficient treatments are missing. Here, we generate the Polg A449T/A449T mouse model, which reproduces the A467T change, the most common human recessive mutation of POLG . We show that the mouse A449T mutation impairs DNA binding and mtDNA synthesis activities of POLγ, leading to a stalling phenotype. Most importantly, the A449T mutation also strongly impairs interactions with POLγB, the accessory subunit of the POLγ holoenzyme. This allows the free POLγA to become a substrate for LONP1 protease degradation, leading to dramatically reduced levels of POLγA in A449T mouse tissues. Therefore, in addition to its role as a processivity factor, POLγB acts to stabilize POLγA and to prevent LONP1-dependent degradation. Notably, we validated this mechanism for other disease-associated mutations affecting the interaction between the two POLγ subunits. We suggest that targeting POLγA turnover can be exploited as a target for the development of future therapies. Graphical Abstract: